2023
DOI: 10.3390/microorganisms11071746
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the Probiotic Potential of Indigenous Moulds and Yeasts in Dry-Fermented Sausages

Micaela Álvarez,
María J. Andrade,
Eva Cebrián
et al.

Abstract: The role of indigenous fungi in the appropriate development of sensory properties and the safety of dry-fermented sausages has been widely established. Nonetheless, their applications as probiotic agents have not been elucidated in such products yet, despite their promising functional features. Thus, it should be interesting to evaluate the probiotic potential of native Debaryomyces hansenii isolates from dry-fermented sausages and their application in the meat industry, because it is the most frequently isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…On the other hand, SR salami revealed a higher count in yeasts and molds. This difference could probably be explained by the faster exhaustion of LAB activity, nonhomogeneous water loss, and uneven mold distribution on the external surface of the SR salami, which could be influenced by the expected metabolic activities [37]. In fact, to produce traditional Italian Salame Napoli, it is ideal that the pH does not fall below the value of 5.2-5.3 even at the end of drying.…”
Section: Microbiological Resultsmentioning
confidence: 99%
“…On the other hand, SR salami revealed a higher count in yeasts and molds. This difference could probably be explained by the faster exhaustion of LAB activity, nonhomogeneous water loss, and uneven mold distribution on the external surface of the SR salami, which could be influenced by the expected metabolic activities [37]. In fact, to produce traditional Italian Salame Napoli, it is ideal that the pH does not fall below the value of 5.2-5.3 even at the end of drying.…”
Section: Microbiological Resultsmentioning
confidence: 99%
“…Although some of them can cause human diseases (such as allergic reactions and fungemia), fungal infections associated with the consumption of food are uncommon (Delgado et al ., 2023 ). On the other hand, several positive effects of yeasts and molds in meat fermentation are known, including the development of characteristic flavors and aromas in the final product, the contribution to the desired texture, and the role in the formation of a mycelial layer protecting the product from light and oxygen and preventing oxidation and rancidity processes and the growth of undesired microorganisms (Álvarez et al ., 2023 ). Indeed, our correlation analysis showed that the fungal abundance was higher where the presence of foodborne pathogens and LAB was lower, indicating a negative correlation between the two microbial components.…”
Section: Discussionmentioning
confidence: 99%